Strategi Marketing Public Relations dalam Memperkuat Brand Awaraness Program Michael Tjandra Luar Biasa di RTV - Tito Laurens; Winda Dwi Astuti Zebua (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Digital media has significantly transformed audience consumption patterns, particularly in the television broadcasting industry. This condition requires local television stations to implement adaptive communication strategies to maintain their existence and strengthen program brand awareness. This study aims to analyze the Marketing Public Relations (MPR) strategy in strengthening brand awareness of the Michael Tjandra Luar Biasa (MTLB) program broadcast on Rajawali Televisi (RTV). The study employs the Marketing Public Relations concept and Thomas L. Harris’s. Three Ways Strategy Theory, comprising push, pull, and pass strategies, along with brand awareness indicators including brand recall, brand recognition, Purchase decisions, and consumption. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation. Informants were selected through purposive sampling, involving internal program personnel and triangulation informants. Data were analyzed through data collection, reduction, display, and conclusion drawing. The findings show that push strategies were implemented through consistent on-air and off-air promotions, pull strategies through social media, digital content, and audience satisfaction analysis, and pass strategies through collaboration with influencers, communities, and sponsors to encourage positive word of mouth. These strategies significantly strengthened MTLB’s brand awareness, particularly in brand recall and consumption. The study concludes that integrated MPR strategies can strengthen television program positioning amid media competition.